Kajian Hidro-Klimatologi Daerah Cirebon-Indramayu-Majalengka- Kuningan (Ciayu Majakuning) - Gunawan, Dodo (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTCase Study of Hidro-Climatology at Cirebon-Indramayu, Majalengka-Kuningan (Ciayu Majakuning). Case Study Water balance calculation has beenconducted in the region of Cirebon, Indramayu, Majalengka and Kuningan or abbreviatednicely as the Ciayu-MajaKuning region. The hidro-climatological component such asevapotranspiration and precipitation were calculated using the NOAH Land-Surface Model(LSM). Model output of monthly data used in the calculation span in the period of 2001-2007.The model has grid box or model resolution of 25 km x 25 km. From the calculation, it is obtainedthat the average of evapotranspiration in this region is 3.1 mm/day or 90 m/month. The maximumvalue of 3.8 mm/day is occurred in May whereas the minimum value of 2.8 mm/day is occurredin December. The highest monthly precipitation occurred in the mountain region (Kuningan)of 450-500 mm/month. In this study area, the period of August-November is the water deficitwhile the period of December-July is the water surplus period in term of water balance. Fromdistrict division point of view, Indramayu is the driest area, and gradually following thetopography height, Kuningan district is the wettest area. Implication of these results to watermanagement aspect is that the dry Area such as Indramayu needs more water supplies byirrigation for agriculture. The sustainable of hydrology cycle path way from Kuningan andMajalengka as the water resources because of highly precipitation to the downstream area(Indramayu and Cirebon) where the precipitation are less is very important in this region.Key words: Water balance, evapotranspiration, hydrology cycle, NOAH-Land-Surface Model